Implementation Of SCM In The Mattress Manufacturing Industry - Sri Wulan Rhamadhani; Nuriadi Manurung; Iin Almeina Lubis (ITEJ (Information Technology Engineering Journals), 2025)
The manufacturing industry is experiencing rapid growth, compelling companies to adopt integrated and technology-driven approaches in managing production and supply chain operations. In the springbed manufacturing sector, where demand is consistently high from household, hospitality, and institutional markets, maintaining efficient supply chain management is essential for sustaining competitiveness and meeting fluctuating market needs. However, many enterprises in this sector still rely on manual processes for inventory tracking, stock reporting, and procurement, which often lead to inefficient resource utilization, increased susceptibility to human error, delays in raw material replenishment, and a decline in customer satisfaction due to unfulfilled orders. This study addresses these challenges by implementing and evaluating a web-based Supply Chain Management (SCM) system as a strategic solution to enhance efficiency, accuracy, and real-time operational control in inventory and distribution processes. Using a qualitative research approach, data were collected through direct observation, structured interviews with key stakeholders, and comprehensive documentation reviews over the course of one year. The system was developed using PHP for backend functionality and MySQL for database management, with the design structured through Unified Modeling Language (UML) to align with specific business workflows and operational requirements. The resulting SCM system integrates supplier order tracking, raw material inventory monitoring, production scheduling, and customer order management into a centralized platform. By automating tasks that were previously manual, the system reduces discrepancies in stock reporting, enhances the traceability of raw materials and finished products, and supports timely decision-making. Additionally, it enables remote access to real-time data, providing improved operational visibility and managerial control. System testing, conducted through iterative validation and performance assessments, demonstrated measurable improvements in data accuracy, inventory turnover speed, and customer order fulfillment rates. The findings suggest that the adoption of a tailored, web-based SCM system can significantly improve operational efficiency for small-scale manufacturing enterprises. Moreover, the study emphasizes the role of digital transformation in strengthening business resilience and adaptability, particularly in mitigating the impact of supply chain disruptions. This research not only offers practical solutions for optimizing supply chain workflows but also serves as a reference framework for similar industries aiming to modernize their inventory and supply chain systems through integrated information technology solutions.